Russia and the West as a conceptual opposition in terms of Russian mentality - Lvov, Alexander (Sociološki pregled, 2023)
The conceptual framework for the discussion the paper introduces is the idea of Russian messianism, which appeared in each period of Russian history, as well as the following characteristic of Russian mentality: the concepts and ideas, which appeared within the domains of social and legal in the West, were interpreted in spiritual and moral context in Russia. The paper traces the development of two aspects of how the conceptual opposition of Russia to the “collective West” was formed. The first aspect is connected with the cultural opposition of Russia to the Western countries in terms of spiritual heredity of the West. The aspect concerns the conceptualization of “the West” as an embodiment of a competitor of Russia in the modifications of the “big project”.
Keywords: Russian messianism; collective West; big project; Russian mentality; katechon